Acute response of well-trained sprinters to a 100-m race: higher sprinting velocity achieved with increased step rate compared with speed training - Otsuka, M.; Kawahara, T.; Isaka, T. (The Journal of Strength and Conditioning Research, 2016)
This study aimed to clarify the contribution of differences in step length and step rate to sprinting velocity in an athletic race compared with speed training. Nineteen well-trained male and female sprinters volunteered to participate in this study. Sprinting motions were recorded for each sprinter during both 100-m races and speed training (60-, 80-, and 100-m dash from a block start) for 14 days before the race. Repeated-measures analysis of covariance was used to compare the step characteristics and sprinting velocity between race and speed training, adjusted for covariates including race-training differences in the coefficients of restitution of the all-weather track, wind speed, air temperature, and sex. The average sprinting velocity to the 50-m mark was significantly greater in the race than in speed training (8.26 ± 0.22 m·s-1 vs. 8.00 ± 0.70 m·s-1, p < 0.01). Although no significant difference was seen in the average step length to the 50-m mark between the race and speed training (1.81 ± 0.09 m vs. 1.80 ± 0.09 m, p = 0.065), the average step rate was significantly greater in the race than in speed training (4.56 ± 0.17 Hz vs. 4.46 ± 0.13 Hz, p < 0.01). These findings suggest that sprinters achieve higher sprinting velocity and can run with higher exercise intensity and more rapid motion during a race than during speed training, even if speed training was performed at perceived high intensity.